simplify (6y+3y^3+2y^2)-(y^2-2y^3-3y)

3 answers

To simplify the expression \((6y + 3y^3 + 2y^2) - (y^2 - 2y^3 - 3y)\), follow these steps:

  1. Distribute the negative sign across the second set of parentheses: \[ 6y + 3y^3 + 2y^2 - y^2 + 2y^3 + 3y \]

  2. Combine like terms:

    • Combine the \(y^3\) terms: \[ 3y^3 + 2y^3 = 5y^3 \]
    • Combine the \(y^2\) terms: \[ 2y^2 - y^2 = y^2 \]
    • Combine the \(y\) terms: \[ 6y + 3y = 9y \]
  3. Write the combined expression: \[ 5y^3 + y^2 + 9y \]

Thus, the simplified expression is: \[ \boxed{5y^3 + y^2 + 9y} \]

Is this true or false?
8(6-2)=30

To determine if the statement \( 8(6-2) = 30 \) is true or false, we first need to evaluate the left side of the equation.

  1. Calculate the expression inside the parentheses: \[ 6 - 2 = 4 \]

  2. Now multiply by 8: \[ 8(4) = 32 \]

Now we can compare the result with the right side of the equation: \[ 32 \neq 30 \]

Thus, the statement \( 8(6-2) = 30 \) is false.

Similar Questions
  1. 1. Simplify 5^-1(3^-2)A. 45 B. 1/45 C. 15^-3 D. 15^2 2. Simplify (3xy^3)^2(xy)^6 A. 9x^8y^12 B. 3x^8y^12 C. 2x^3y^12 D. 9x^8y^9
    1. answers icon 7 answers
  2. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
more similar questions